2020
DOI: 10.1038/s41419-020-2306-6
|View full text |Cite
|
Sign up to set email alerts
|

Blocking the autocrine regulatory loop of Gankyrin/STAT3/CCL24/CCR3 impairs the progression and pazopanib resistance of clear cell renal cell carcinoma

Abstract: The poor prognosis of clear-cell renal cell carcinoma (ccRCC) patients is due to progression and targeted drug resistance, but the underlying molecular mechanisms need further elucidation. This study examined the biological function and related mechanisms of gankyrin in ccRCC based on the results of our previous study. To this end, in vitro functional experiments; in vivo models of subcutaneous tumor formation, lung metastasis, and orthotopic ccRCC; and antibody chip detection, co-IP, ChIP assays were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Our previous study showed that gankyrin is an oncoprotein that is frequently up‐regulated in OS 5 . In addition, increasing evidence suggests that gankyrin is involved in the occurrence and progression of various tumours 6‐8 . Nevertheless, the potential role of gankyrin in OS metastasis is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that gankyrin is an oncoprotein that is frequently up‐regulated in OS 5 . In addition, increasing evidence suggests that gankyrin is involved in the occurrence and progression of various tumours 6‐8 . Nevertheless, the potential role of gankyrin in OS metastasis is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although a high level of eotaxin mRNA expression was detected in Hodgkin lymphoma, especially nodular sclerosis [ 18 ], eotaxin was expressed on fibroblasts rather than Hodgkin/Reed-Sternberg cells themselves [ 19 ]. Eotaxin-3 mRNA expression was detected in some cases of follicular lymphoma [ 20 ], and multiple reports on cancers associated with eotaxin-2 expression exist [ 21 23 ]. In clear cell renal cell carcinoma, patients with high eotaxin-2 expression had poor survival rates [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eotaxin-3 mRNA expression was detected in some cases of follicular lymphoma [ 20 ], and multiple reports on cancers associated with eotaxin-2 expression exist [ 21 23 ]. In clear cell renal cell carcinoma, patients with high eotaxin-2 expression had poor survival rates [ 21 ]. In hepatocellular carcinoma, eotaxin-2 contributes to malignancy via the angiogenesis pathway and indicates a poor prognosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that targeted treatment for advanced and metastatic ccRCC has been fully developed, response to treatment is diverse [ 12 ]. Identification of molecular mechanisms and relevant prognostic factors may be critical to the treatment of ccRCC [ 13 ]. The prognosis of the tumor is closely connected with TME, particularly when considering the tumor immune microenvironment [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%